The Effectiveness of Use of Upanat in Supporting Sustainable Tourism at Borobudur Temple - Fifiyanti, Debby; Henriques, Arvela Firsta; Putra, Pniel Gandyanto Andhika (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
The Upanat is a special type of footwear designed specifically for climbing the structure of the Borobudur Temple. The design of the Upanat focuses on sponge-type footwear, material resistance to physical and chemical processes, and wearing comfort. The primary purpose of using Upanat is to minimize the friction between the temple stones and footwear, thus preventing wear and tear and maintaining the structure of the Borobudur Temple. This study aimed to determine the effectiveness of using Upanat at the Borobudur Temple, and a descriptive qualitative approach was used to collect data through direct interviews, observations, and documentation. The determination of the effectiveness of Upanat use at the Borobudur Temple was carried out in three stages: reducing data, presenting data, and drawing conclusions. The results of this research show that Upanat is highly effective in reducing wear and tear on the stairs and floors of the Borobudur Temple, as it uses materials that cause minimal friction.